Análise das competências digitais de professores de matemática do ensino fundamental em um curso de formação docente - Vasconcelos, Sarah Pires Barreto de Souza (2024)
The emergence of Digital Information and Communication Technologies (ICT) and the consolidation of the digital environment caused significant changes in interactions between individuals and in teaching and learning methods. In the educational sphere, the integration of ICT presents new perspectives and challenges for the pedagogical work of mathematics teachers. In this sense, it is essential that these teachers acquire essential digital skills to fully explore the potential of these technologies in improving and innovating their pedagogical practice. Therefore, the objective of this research is to analyze the responses of elementary school mathematics teachers based on the application of the European Framework for the Digital Competence of Educators (DigCompEdu) in a Continuing Training Course for teachers, with the aim of identifying the use of technologies by these professionals and whether it makes a difference in their teaching. A quantitative and qualitative case study of an exploratory nature was carried out, in an asynchronous teacher training course, in which 1332 elementary school mathematics teachers were mapped. The data collection process began with the application of a questionnaire on the personal and professional profile of mathematics teachers, followed by the second questionnaire, the DigCompEdu-Check-In. After carrying out the study, it was possible to verify, through the data obtained, the personal and professional profile of mathematics teachers. It is also observed that, before applying the DigCompEdu questionnaire, some teachers classified themselves at level A2 – Explorer, and others at level B1 – Integrator. However, at the end of the questions, there was a predominance at level B1 – Integrator, while the others were at level A2 – Explorer. And finally, it can be seen that the teachers actually fit into the proficiency level B1 – Integrator.